Free radical scavenging capacity and antioxidant activity of cochineal (Dactylopius coccus C.) extracts - González, Evangelina A. (2010)
Carminic acid (CA) is a natural red pigment produced by Dactylopius coccus C. insects. It is widely used in the food industry to replace synthetic colourants. Despite being known for a long time, its antioxidant properties have not been studied so far. The aim of this study was to determine CA activities by different methods namely, free radical scavenging capacity against DPPH and ABTS radicals as well as its inhibition ability of β-carotene bleaching enzymatically induced by lipoxygenase (LOX). CA exhibited a remarkable antiradical activity similar to that of known antioxidants such as quercetin, ascorbic acid and trolox. Effectiveness of CA to protect β-carotene in the co-oxidation with linoleic acid is attributed to enzymatic inhibition of LOX rather than peroxyl radical trapping.